Anatomical and biomechanical evaluation of the lateral calcaneo-cuboid and bifurcate ligaments. Issue 8 (December 2022) - Baumbach, Sebastian F.; Kistler, Manuel; Gaube, Federico P.; Bartz, Benjamin; Traxler, Hannes; Throckmorton, Zach; Böcker, Wolfgang; Polzer, Hans
Abstract: Background: This study aims to analyze the ligaments of the dorso-lateral calcaneo-cuboid joint and to assess the biomechanical relevance of the bifurcate ligament. Methods: 16 specimens were analyzed for their ligamentous anatomy of the dorso-lateral calcaneo-cuboid joint and side-alternating assigned to two groups with varying ligamentous dissection order. The Chopart joint was stressed in plantar, medial, and lateral direction measuring the displacement by an 3D motion tracker for every dissection step. Results: 37.5% of specimens had all ligaments (lateral calcaneo-cuboid, dorsal calcaneo-cuboid, bifurcate calcaneo-cuboid, bifurcate calcaneo-navicular), 37.5% were lacking bifurcate´s calcaneo-cuboid-portion, and 25% presented without dorsal calcaneo-cuboid. Biomechanical testing revealed no significant displacement within the calcaneo-cuboid or talo-navicular joint for any stressed state except for axial compression with dissected dorsal talo-navicular joint capsule in Group 2. Conclusion: Broad morphological variability and missing significant displacement regardless of its integrity, make the bifurcate ligament appear of limited biomechanical relevance.